Cabaran arah perubahan kini dalam geografi fizikal di Malaysia - Sharifah Mastura SA, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2005)
The purpose of this paper is to overview recent trends in physical geography as thought and practised in the Geography Department of the Universiti Kebangsaan Malaysia and outside it, in particular, the United Kingdom. While highlighting the blessings of state-of-the-art geotechnologies such as sophisticated computer, sattelite, GIS, and multi-media technologies the paper sums up a fivefold implications of the current trends on the teaching and practice of physical geography in Universiti Kebangsaan in particular, and in Malaysia in general: (1) applied and management studies become the meeting grounds of physical and human geographies; (2) physical geographers need to enhance their scientific acumen to achieve excellence; (3) the imperative of physical geography utilising state of the art geotechnologies to enhance measurement and monitoring precision; (4) the curriculum of physical geography needs to be restructured so as to accommodate new research methods, problem solving skills, critical thinking, and commendable ethics; and (5) the need to balance between holism and specialism with regard to geomorphology,climatology and biogeography